Existence of solutions for second-order evolution inclusions. (1994) - Papageorgiou, Nikolaos S.
Abstract : In this paper we examine second-order nonlinear evolution inclusions and prove two existence theorems; one with a convex-valued orientor field and the other with a nonconvex-valued field. An example of a hyperbolic partial differential inclusion is also presented.